2017
DOI: 10.18632/oncotarget.19400
|View full text |Cite
|
Sign up to set email alerts
|

The 30 kb deletion in the APOBEC3 cluster decreases APOBEC3A and APOBEC3B expression and creates a transcriptionally active hybrid gene but does not associate with breast cancer in the European population

Abstract: APOBEC3B, in addition to other members of the APOBEC3 gene family, has recently been intensively studied due to its identification as a gene whose activation in cancer is responsible for a specific pattern of massively occurring somatic mutations. It was recently shown that a common large deletion in the APOBEC3 cluster (the APOBEC3B deletion) may increase the risk of breast cancer. However, conflicting evidence regarding this association was also reported. In the first step of our study, using different appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 89 publications
(143 reference statements)
0
26
0
Order By: Relevance
“…This locus was shown to be significantly associated with breast cancer risk in different populations including those of Chinese, Iranian, and European ancestries [ 18 , 47 , 48 ]. It was demonstrated also that deletion in the APOBEC3 loci disrupting APOBEC3A and APOBEC3B genes lead to the decreased expression of the corresponding genes [ 66 , 67 ]. Moreover, the association between GSTT1 gene deletion and breast cancer risk has been widely studied and it was demonstrated that GSTT1 null genotype is associated with increased breast cancer risk [ 68 ] and also with significant downregulation of GSTT1 gene resulting in loss of protein expression [ 69 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…This locus was shown to be significantly associated with breast cancer risk in different populations including those of Chinese, Iranian, and European ancestries [ 18 , 47 , 48 ]. It was demonstrated also that deletion in the APOBEC3 loci disrupting APOBEC3A and APOBEC3B genes lead to the decreased expression of the corresponding genes [ 66 , 67 ]. Moreover, the association between GSTT1 gene deletion and breast cancer risk has been widely studied and it was demonstrated that GSTT1 null genotype is associated with increased breast cancer risk [ 68 ] and also with significant downregulation of GSTT1 gene resulting in loss of protein expression [ 69 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…A genome-wide association study in the Chinese population demonstrated the A3B deletion is associated with BRCA (odds ratio (OR) 1.3 one-copy, 1.8 two-copy deletion, p = 2.0 × 10 −24 ) [ 155 ], which was replicated in a European population (OR 1.2 one-copy, 2.3 two-copy deletion, p = 0.005) [ 156 ]. However, including familial BRCA for the first time, a later study showed a lack of association of the A3B deletion with BRCA risk, which was independently validated in three European cohorts (in total: 2972 cases and 3682 controls) [ 157 ]. This study provided direct evidence for the generation of the transcriptionally active hybrid gene A3A/A3B from the allele with the A3B deletion and confirmed the suggested structure of A3A/A3B transcript, which enabled A3A, A3B and A3A/A3B expression levels to be distinguished.…”
Section: A3 Enzymes and Cancermentioning
confidence: 99%
“…A3H Hap I was identified to induce genomic mutations specifically in lung cancer 13 . Interestingly, the activity of A3H Hap I was found because researchers wanted to investigate how genomic mutations with a cytidine deaminase signature were still occurring in people with an A3B-/-deletion [51][52][53][54] , which occurs in the world population at 22.5%, although it primarily occurs in Oceanic populations 44 . Although A3A is also involved in cancer mutagenesis, it appears to be strongly associated with breast cancer 31,55 .…”
Section: Discussionmentioning
confidence: 99%